2021
DOI: 10.1177/0885328220988427
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of chondroitin sulfate nano-selenium on chondrocyte of patients with Kashin-Beck disease

Abstract: Objective To investigate the protective effect of chondroitin sulfate nano-selenium (SeCS) on chondrocyte of Kashin-Beck disease (KBD). Methods Chondrocyte samples were isolated from the cartilage of three male KBD patients (54–57 years old). The chondrocytes were respectively divided into four groups: (a) control group, (b) SeCS supplement group (100 ng/mL SeCS), (c) T-2 + SeCS supplement group (20 ng/mL T-2 + 100 ng/mL SeCS), and (d) T-2 group (20 ng/mL T-2). Live/dead staining and transmission electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Two enzymes related to chondroitin sulfate (CS, one basic component of ECM) metabolism [ 29 , 34 ], CHST-3 and CHST-4, were also identified as differentially expressed N-glycoproteins. CHST-3 is a type II transmembrane protein with six N-glycosylation sites and catalyzes the transfer of sulfate to position 6 of GalNAc residues of CS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two enzymes related to chondroitin sulfate (CS, one basic component of ECM) metabolism [ 29 , 34 ], CHST-3 and CHST-4, were also identified as differentially expressed N-glycoproteins. CHST-3 is a type II transmembrane protein with six N-glycosylation sites and catalyzes the transfer of sulfate to position 6 of GalNAc residues of CS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, oral sodium selenite is the primary methods used for Se supplementation ( 125 ). Chondroitin sulfate nano-selenium has been tested as a supplement of selenium ( 126 ). Se supplementation has a significant impact on the treatment of KBD.…”
Section: Prevention and Treatment Of Kbdmentioning
confidence: 99%
“…Fatima et al also discovered that moderate concentrations of Se nanoparticles can enhance the survival and osteogenic potential of human mesenchymal stem cells by mitigating oxidative stress ( 129 ). Qiao et al found that chondroitin sulfate nano-selenium supplement increased the number of living chondrocytes, improved the ultrastructure, and altered the expressions of chondroitin sulfate structure-modifying sulfotransferases, Caspase-9, and Cyt-C ( 126 ). However, the literature is scarce on the green synthesis of Se nanoparticles, necessitating further investigation into the interplay between Se and Se nanoparticles, as well as elucidation of the underlying biological pathways responsible for their differential therapeutic efficacy.…”
Section: Prevention and Treatment Of Kbdmentioning
confidence: 99%